Which Firms Benefit from Corporate QE during the COVID-19 Crisis? The Case of the ECB's Pandemic Emergency Purchase Program - Demirgüç-Kunt, Asli (World Bank, Washington, DC, 2020)
Using an event study methodology, this paper examines how European firms have been affected by the announcement of the European Central Bank's Pandemic Emergency Purchase Program (PEPP). Firms with an investment grade rating benefit relatively more, as evidenced by higher share prices and lower credit default swap spreads, which reflects that the European Central Bank is restricted to purchasing investment grade corporate debt securities. The gains to shareholders relative to the total gains of shareholders and debtholders are negatively related to firm leverage, consistent with the existence of debt overhang. Firms that are more heavily impacted by the pandemic benefit relatively little from the PEPP, which could reflect that the business models of some of these firms heavily damaged by the pandemic. Monetary policy in the form of the PEPP and national fiscal responses to the pandemic are shown to be complements in the sense that a strong pre-PEPP fiscal response enhances the potential for the program to have a positive effect on equity and debt valuations.